High altitude solar UV-B and abscisic acid application increase grape berry antioxidant capacity - Berli, Federico Javier (2015)
It has been proposed that ultraviolet-B (UV-B) radiation activates grapevines antioxidant defense system and abscisic acid (ABA) acts downstream in the signaling pathway. Effects of solar UV-B perceived by high altitude vineyards and ABA sprays on berry quality indicators and fruit yield were studied on Vitis vinifera L. cv. Malbec at 5 developmental stages during three consecutive growing seasons. Grapevines were exposed to ambient solar UV-B (+UV-B) or to UV-B filtered sunlight (?UV-B) from 15 days before flowering, combined with weekly sprays of 1 mM ABA (+ABA) or H2O (?ABA) from 27 days before veraison. Berry skin phenols (anthocyanins and total polyphenols) were increased by +UV-B and +ABA, markedly in concentration (UV-B x ABA significant interaction). The increases in antioxidant capacity, measured as oxygen antioxidant capacity (ORAC) and phenols in the berries exposed to +UV-B/+ABA combined treatment were higher compared with ?UV-B/?ABA, for the same increase in sugar. Also, +UV-B and +ABA interact to reduce number of berries and bunches weight (fruit yield), without affecting sugar concentration (smaller berries) at harvest. Antioxidant compounds (protective for plants), are triggered in +UV-B/+ABA at the expenses of sugar accumulation, berry retention and growth (fruit yield). UV-B perceived by high altitude vineyards and ABA applications interact to increase red grape berry quality indicators, markedly in concentration (important from a winemaking standpoint). Also, UV-B and ABA effects on berry sugar accumulation and growth depend on the stage of development.